Individualizing Therapy in CIDP: A Mini-Review Comparing the Pharmacokinetics of Ig With SCIg and IVIg - Beydoun, Said R.; Sharma, Khema R.; Bassam, Bassam A.; Pulley, Michael T.; Shije, Jeffrey Z.; Kafal, Ayman (Frontiers in Neurology, 2021)
Immunoglobulin (Ig) therapy is a first-line treatment for CIDP, which can be administered intravenously (IVIg) or subcutaneously (SCIg) and is often required long term. The differences between these modes of administration and how they can affect dosing strategies and treatment optimization need to be understood. In general, the efficacy of IVIg and SCIg appear comparable in CIDP, but SCIg may offer some safety and quality of life advantages to some patients. The differences in pharmacokinetic (PK) profile and infusion regimens account for many of the differences between IVIg and SCIg. IVIg is administered as a large bolus every 3–4 weeks resulting in cyclic fluctuations in Ig concentration that have been linked to systemic adverse events (AEs) (potentially caused by high Ig levels) and end of dose “wear-off” effects (potentially caused by low Ig concentration). SCIg is administered as a smaller weekly, or twice weekly, volume resulting in near steady-state Ig levels that have been linked to continuously maintained function and reduced systemic AEs, but an increase in local reactions at the infusion site. The reduced frequency of systemic AEs observed with SCIg is likely related to the avoidance of high Ig concentrations. Some small studies in immune-mediated neuropathies have focused on serum Ig data to evaluate its potential use as a biomarker to aid clinical decision-making. Analyzing dose data may help understand how establishing and monitoring patients' Ig concentration could aid dose optimization and the transition from IVIg to SCIg therapy.